Improvement Operational Business Process in Logistic Companies Using Model-Based and Integrated Process Improvement - Aritonang, Adhe Martha Veronika; Ciptomulyono, Udisubakti (Hasanuddin Economics and Business Review, 2024)
The logistics business sector is experiencing increasingly competitive and complex developments, requiring enhancements to remain competitive. The method used in this research is the Model-Based and Integrated Process Improvement (MIPI) method, and business process mapping using Business Process Model and Notation. The MIPI method consists of four stages: Understand Business Needs, Understand the Process, Model and Analyze Process, by conducting activity analysis using Value-Added Analysis and Cause and Effect Analysis to identify problem causes, and the final stage is Redesign Process. Value-Added Analysis indicates that in the outbound process, there are 21 activities, comprising 4 Real Value Added, 15 Business Value Added, and 2 Non-Value Added. In the inbound process, there are 21 activities with a composition of 2 Real Value Added, 16 Business Value Added, and 3 Non-Value Added. Based on Cause and Effect Analysis, customer complaints were found to be related to delayed delivery of goods, with root causes identified in planning, methods, equipment, and human factors. Based on these findings, a proposal for a new business process design is made, including the elimination of Non-Value Added activities and parallelism in some activities to simplify Business Value Added activities. Recommendations for these issues include expanding partnerships and collaboration with vendors, increasing fleet size, and providing employee development training.